London’s Great Starfish: The Construction of Mid-Victorian Suburban Fiction - Tamara Silvia Wagner (Cahiers Victoriens et Edouardiens)
In Trollope's 1858 The Three Clerks, the coming of commuter railways generates a peculiarly modern image of suburbanised, starfish-like, London: ‘London will soon assume the shape of a great starfish. . . . .The old town, extending from Poplar to Hammersmith, will be the nucleus, and the various railway lines will be the projecting rays.’ It is an outgrowth only to be understood as an otherworldly creature: from some undefined depths of alterity, an exotic animal rises to finger the English countryside. The centrality of changing urban space in Victorian literature and culture has spawned some of the best interdisciplinary research, but precisely this concentration on the city has elided suburbia's significance. In discussions of urban modernity, suburbs are marginalised; clichéd images of bourgeois self-confinement failing to raise more than a passing interest in these margins. What was new and different about Victorian suburbia and how the cultural fictions that have shaped our understanding of what constitutes ‘suburbanism’ were created are rarely addressed issues. At the mid-nineteenth century, however, ‘the suburban’ formed an expanding field for fictional explorations in which the association between urbanisation and ventures into foreign spaces powerfully drew into debate the promotion of ‘suburbanism’ as the ultimate manifestation of the divorce of home and workplace. The construction of suburban fiction operated within a negotiation of domesticity and alterity that brought home the potentials and problems associated with urban expansion. In cutting across subgenres, it engendered some of the most pervasive clichés, but in an ambiguous process of redefinition that impels us to reconsider still current cultural myths. Writers as different as Anthony Trollope, Charles Dickens, Wilkie Collins, and also the little-known domestic novelist Emily Eden made the most of what had become a rapidly evolving space characterised by immense fluidity. They did so in markedly divergent ways that evince the versatility of suburban fiction.